CONSUMER ACCEPTABILITY OF BANANA BLOSSOM SISIG - Isabel F Salvador (UNEJ e-Proceeding, 2012)
This study assessed the consumer acceptability of banana blossom “sisig” at IsabelaState University, Echague, Isabela, Philippines for the School Year 2011-2012. The studyused a descriptive form of research which described the level of evaluations of the tasterson the banana blossom “sisig” in terms of variables such as appearance, color, texture,aroma, presentation, and taste. In analyzing the data gathered the 9-point hedonic scalewas used. Evaluation of the product was done when respondents are grouped by theirprofile. The data taken from the evaluations were analyzed using frequency counts andpercentages, means, t-test and Analysis of Variance. The highlight of the study were asfollows: a) the sensory evaluation of the respondents in all the variables ranges from “likevery much” to “like extremely” regardless of any profile variable; b) the respondents’category influences their evaluations in taste but has nothing to do on the rest of thevariables; c) the profiles of the respondents do not affect their evaluations in the differentvariables; d) there is a positive Return on Investment in the commercialization of bananablossom sisig. Based on result of the study it revealed that the appearance and taste is “likeextremely” and the color, texture, aroma as well as presentation is “like very much” by thetasters.